2019
DOI: 10.1136/bmjqs-2018-008926
|View full text |Cite
|
Sign up to set email alerts
|

The discontinuation of contact precautions for methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus: Impact upon patient adverse events and hospital operations

Abstract: BackgroundContact precautions for endemic methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) are a resource-intensive intervention to reduce healthcare-associated infections, potentially impeding patient throughput and limiting bed availability to isolate other contagious pathogens. We investigated the impact of the discontinuation of contact precautions (DcCP) for endemic MRSA and VRE on patient outcomes and operations metrics in an acute care setting.MethodsThis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…[4][5][6] Despite this, CP are now widely implemented worldwide 2 , even though there is little evidence that they are more effective than standard IPC precautions (including antimicrobial stewardship, hand hygiene, environmental and equipment cleaning, and aseptic technique) 7 in preventing MRSA acquisitions and infections in hospital. [8][9][10]…”
Section: The Emergence Of Mrsa and Invention Of Contact Precautionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] Despite this, CP are now widely implemented worldwide 2 , even though there is little evidence that they are more effective than standard IPC precautions (including antimicrobial stewardship, hand hygiene, environmental and equipment cleaning, and aseptic technique) 7 in preventing MRSA acquisitions and infections in hospital. [8][9][10]…”
Section: The Emergence Of Mrsa and Invention Of Contact Precautionsmentioning
confidence: 99%
“…31 Similarly, the aggregated financial costs of the application of CP for the management of MRSA will have been significant. 8,10 Whilst the environmental impact of the PPE required for CP had not previously attracted attention, the environmental impact of PPE manufacture, supply and disposal has recently been noted. 32 Crucially, whilst SARS-CoV-2 control measures have likely reduced COVID-19 hospitalisations, and deaths, 12 strong evidence for the efficacy of CP in preventing MRSA transmission does not exist.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that effective interventions link a defined population to appropriate capacity through an efficient process: ineffective interventions were found to have neglected one or more of these three crucial aspects. The model is gaining currency [21][22][23] but has not yet been applied to in-depth analysis of a family of interventions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…10 With this concern, several studies have reported no significantly increased incidence of MDRO after discontinuation of contact isolation with horizontal infection control interventions such as daily chlorhexidine gluconate bathing. [11][12][13] Subsequent studies also reported higher incidences of adverse events among contact isolation patients using different study designs such as retrospective cohort, 14 observational quasi-experimental, 15 and propensity score-matched cohort. 16 Conversely, few studies provided counterevidence that contact isolation patients were less likely to experience preventable adverse events.…”
Section: Introductionmentioning
confidence: 99%